Screening for pectinolytic activity of wood-rotting basidiomycetes and characterization of the enzymes - Xavier-Santos, S. [UNESP]; Carvalho, C. C. [UNESP]; Bonfá, M. [UNESP]; Silva, R. [UNESP]; Capelari, M.; Gomes, E. [UNESP] (Springer Nature, 2004)
Seventy-five fungal strains from different groups of basidiomycetes, newly isolated from rotten wood, were screened for pectinolytic activity. Despite the fact that basidiomycetes are scarcely referred to as pectinase producers, the polygalacturonase (PG) activity was detected in 76 % of the strains; 16 % with activity higher than 40 nkat/g, 40 % between 13.3 and 40 nkat/g, and 44 % with activity lower than 13.3 nkat/g. The highest productions were obtained among the fungi from order Aphyllophorales, family Polyporaceae. The characterization of the enzymes from the highest PG producers (Lentinus sp., Gloeophyllum striatum, Pycnoporus sanguineus, Schizophyllum commune) showed optimum temperature for catalytic activity at 60-70°C and two peaks of pH optimum (3.5-4.5 and 8.5-9.5). The enzymes exhibited high pH stability (3.0-11.0) but after incubation at 40°C for 1 h their activity dropped by 18-73 %.
Keywords: pectin; polygalacturonase; Basidiomycetes; enzyme stability; enzymology; isolation and purification; Lentinus; metabolism; microbiology; pH; Polyporaceae; temperature; wood; Basidiomycota; Environmental Microbiology; Enzyme Stability; Hydrogen-Ion Concentration; Lentinula; Pectins; Polygalacturonase; Schizophyllum; Temperature; Wood; Aphyllophorales; Fungi; Gloeophyllum; Pycnoporus sanguineus; Schizophyllum commune